Does Water Cleaning Mitigate Atmospheric Degradation of Unstable Heritage Glass? An Experimental Study on Glass Models - Thalie Law; Odile Majérus; Marie Godet; Mélanie Moskura; Thibault Charpentier; Antoine Seyeux; Daniel Caurant (Heritage, 2025)
Glass curators often question how their treatments affect the long-term stability of historical glass. While damp cotton swabs are commonly used to remove surface salts and dust, the use of water remains controversial, particularly for heavily altered glass, due to concerns about worsening hydration. This study investigates the effect of water rinsing on an unstable soda-lime glass altered for six months (monoliths) and fifteen months (powders) at 35 °C and 85% relative humidity. Samples were then rinsed with Milli-Q water at 20 °C or 50 °C, and the monolithic glass was subsequently subjected to an additional 15 months of alteration under the same conditions. The glass surface was characterized by optical and scanning electron microscopy (SEM) as well as Raman spectroscopy to identify the nature of the salts. The evolution of the hydrated layer was assessed using transmission FTIR, Raman and solid-state NMR spectroscopies, ToF-SIMS, and thermogravimetric analysis (TGA). The results show that rinsing effectively removes surface salts—primarily sodium carbonate—and induces structural changes in the hydrated layer, promoting silicate network polymerization. Upon resuming alteration, rinsed monolithic samples exhibit no further degradation after the additional 15 months of alteration. These findings offer promising insights for conservation practices and may help curators refining their treatment strategies for altered glass.